The expression (a+b) + (a-b) can be rewritten as a + b + a - b = 2a.There is no need to use absolute value.
When factored it is: 12(A+b)
it think ot is 5(a+b)
It is: b+b+b = 3b
3+2*A+B*4/2-4 = 3 + 2A + 2B - 4 = 2A + 2B - 1
7
The expression (a+b) + (a-b) can be rewritten as a + b + a - b = 2a.There is no need to use absolute value.
When factored it is: 12(A+b)
it think ot is 5(a+b)
b + 1 is b plus 1 as an algebraic expression.
The expression 2a + b represents the sum of two terms, where 2a is equivalent to "two times a" and b is simply b. To simplify this expression, you would combine the like terms, which in this case are 2a and b. Therefore, the simplified form of 2a + b is simply the sum of 2a and b, which cannot be further simplified.
It is: b+b+b = 3b
The answer is b+1. Therefore the algebraic expression for this is b+1
A - B = A + (-B) A - B = A + (-B) A - B = A + (-B) A - B = A + (-B)
It is simply as stated in the question. Without information about a or b, the expression cannot be simplified nor evaluated.
The value of a + b depends on the values of the individual variables.The expression a + b cannot be simplified.
It is an algebraic expression in the form of: b+14